Collaborative E-Learning for Tangerang Vocational High School - Didi Kurnaedi; Setyawan Widyarto; Saliyah Kahar (Tech-E, 2022)
Information technology is no stranger in modern times. The emergence of various learning media has promoted the application of communication and information technology learning media called e-learning in vocational high schools (SMK). E-learning is learning that uses technology. The E-Learning of Tangerang Vocational High School (SMK) uses independent E-Learning learning media. In this research, the methods used are descriptive qualitative and descriptive statistical analysis. The research goal is to develop a collaborative E-Learning learning model for Tangerang Vocational High School (SMK) as a learning model. The sample included 375 students and 22 vocational high schools (SMK) Tangerang.